Standard Operating Procedure (SOP): weed control and management - Ayankanmi, T.; Iluebbey, P.; Kulakow, P.; Parkes, E.; Rabbi, I.; Akpotuzor, P.; Olaniyo, E.; Oke, E. (International Institute of Tropical Agriculture, 2024)
Weed control and management are well-planned field operations carried out to prevent, remove, or limit weed infestations so the crops can grow to attain high productivity. The primary goal of weed control is to manage the vegetation in a way that will promote the growth of plants that are beneficial to humans and the suppression of unwanted plants.